(untitled) (PIONIR: JURNAL PENDIDIKAN, 2021)
Student Management is the management and arrangement of students in schools or madrasah starting from the analysis of student needs, placement to graduation and alumni of these students. The focus of this research includes, planning of students, organizing students, coaching and developing students at MAS Ulumuddin. The results of the study showed that planning in the stage of analyzing the needs of new students at MAS Ulumuddin was very good with the mapping of needs and facilities for learning places and dormitories owned by MAS Ulumuddin, study rooms that already had complete learning facilities and infrastructure. The organization of students at MAS Ulumuddin is carried out by grouping based on their respective gender, age, talent, interests and abilities, grouping students in various criteria and benchmarks determined by MAS Ulumuddin, including the type of male calamine will be assigned Separate placement by female gender, as well as classifying abilities based on the results of grades and rankings after the selection process to be placed in certain classrooms. Coaching and development of students at MAS Ulumuddin is carried out through strategies and approaches that include: a) Integrating values and ethics in santri subjects at school, b) Internalizing positive values instilled by all school members, c) Habituation and training, d) Giving examples and examples, e) Creating an atmosphere of character in schools, f) Cultivating. g) law enforcement of student and student courts to those who violate.